Shaping the Profession – And Reshaping Socio-Political Inclusion - Tiziana Faitini (Soft Power, 2024)
The figure of the “professional” looms large in contemporary neoliberal societies as an ideal for economic activity and socio-political inclusion, and even as a model for individual self-development, in spheres of existence extending far beyond the limited circle of the specific types of (traditional and liberal) occupations. But how and when did this figure arise? What has led professional activity to become such an essential part of our personal, social, moral, economic, and political life?